The Silent Architects: How Managerial Reciprocity Shapes the Psychological Landscape of Primary Teachers - Citra Pitaloka; Marzuki Noor; Sujino Sujino (Assyfa Learning Journal, 2026)
High occupational demands placed on educators frequently impair their psychological flourishing and professional productivity. Conventional workload allocation operates predominantly through rigid administrative hierarchies, often lacking a mutual support framework between school leaders and teaching staff. Incorporating the mubadalah perspective of reciprocal justice, this study investigated the empirical effect of managerial workload allocation on primary school teachers' well-being. Utilizing an explanatory quantitative approach with an ex post facto design, the inquiry evaluated a proportional cluster random sample of 62 elementary educators derived from an initial population of 166 teachers. Data gathered via validated and highly reliable Likert-scale questionnaires were subjected to simple linear regression analysis. Descriptive metrics revealed that managerial workload handling reached a good level (mean = 136.71; SD = 13.11), whereas teacher well-being scored at a moderate benchmark (mean = 66.76; SD = 6.36). Hypothesis testing confirmed a statistically significant positive effect (p = 0.007 < 0.05) with a coefficient of determination (R2) of 0.606. Consequently, structural enhancements in reciprocal workload management directly elevate teachers' psychological well-being. These findings imply that school principals must transition from purely administrative task distribution toward communicative, fair, and reciprocal workload stewardship, while encouraging teachers to actively engage in collaborative task management to foster a resilient educational ecosystem.